Evaluation of extruded snacks from blends of acha(Digitaria exilis) and cowpea(Vigna unguiculata) flours (2012)
"The production of acha and cowpea are the complementary food and are produced in large quantities in Nigeria, which are the major sources of protein and carbohydrate respectively. The study was proposed on developed high protein-energy complementary foods from the blends of cowpea and acha using extrusion cooking. Cultivars of cowpea (IT90K-277-2) and acha (cream colour) were selected and milled into flours. Using the response surface methodology, the blends of acha and cowpea flours at 70:30 and 60:40 respectively were extruded using a single screw extruder at barrel temperature of 120-160•C and feed moisture content of 18-25% (d.b). The proximate composition and trypsin inhibition activity of the extrudates and blends were determined, while compressive forces were determined using testometric analysis.The protein content increased from 7.98% for acha flour to 16.03% and 18.73% for blends containing 30.0% and 40.0% cowpea respectively. Trypsin inhibition activity of the blends decreased by 76.0% to 92.1% as a result of the increasing extrusion temperature and feed moisture content. Compression forces at the peak, break and yield of extrudates' ranged from 148.3 to 886.4 N, 140.2 to 882.5 N and 96.3 to 226.4 N respectively. Extrusion cooking parameters (barrel temperature, feed moisture content and feed composition) significantly affected the quality of the cowpea-acha blends."